ANALYSIS OF ISLAMIC COMMUNICATION IN PREVENTING ACTS OF VIOLENCE AGAINST WOMEN AND CHILDREN IN LABUHANBATU DISTRICT - Batubara, Hafsah Juni; Sazali, Hasan; Simamora, Irma Yusriani (al-Balagh : Jurnal Dakwah dan Komunikasi, 2025)
The rate of violence against women and children is still very high in Indonesia, including in Labuhan Batu. Based on the research conducted, there have been many studies on preventing acts of violence against women and children, but few have seen the benefits of Islamic communication in the implementation process. This study uses qualitative methods and descriptive phenomenological data analysis to reveal the implementation of Islamic communication in handling violence against women and children. In-depth interviews are data collection methods. The research results show that DPPPA communication in prevention and treatment service tasks uses Islamic communication with good speech, an attitude full of gentleness, adapting language and content, conveying information about the actual situation, prioritizing empathy, and building good relationships. The results of the prevention phase of UU TPKS advocacy activities, outreach on ABH prevention, improvement of the Children's Forum and Puspa communication forum, increasing the role of PATBM , special SIMFONI PPA training, case management training, protecting children from abuse, and monitoring child-friendly information in internet cafes in the Rantauprapat area. This study shows that DPPPA Labuhanbatu Regency's communication regarding implementation and prevention results has been carried out well. To stop acts of violence against women and children in Labuhanbatu Regency, they must truly implement Islamic communication, not just fulfill their duties at work.